Dielectric properties of laser-induced conditions in a hybrid composite made by doping a side-chain liquid crystalline polymer - San, SE; Okutan, M; Köysal, O; Ono, H (Elsevier, 2005)
A side-chain liquid crystalline polymer (SLCP) was investigated by measuring the laser-induced effects on molecular reorientation. A 20 mW He-Cd (lambda = 441.6 nm) laser was used as a pumping source during the measurements, which were performed by an impedance analyzer to see the effect of laser illumination on the polymer-doped and non-polymered samples. Dielectric anisotropy dependency is quantitatively estimated via capacitive measurements. Our results show that laser pumping causes a considerable decrease in the required amount of voltage for reorientation in the constructed SLCP composite. (c) 2005 Elsevier B.V. All rights reserved.
3rd International Conference on Broadband Dielectric Spectroscopy and its Applications -- AUG 23-26, 2004 -- Delft, NETHERLANDS
Keywords: Dye; Spectroscopy; Diffraction; Relaxation; Phase